Atlante - Ferretti, Emanuela; Giannotti, Alessandra; Mozzo, Marco; Castellini, Marta (Opus Incertum, 2019)
In order to provide exhaustive documentation concerning the “Cave of the Animals”, the atlas is composed of already known historical documents, as well as of new historical and scientific insights. In the first case, we provide some important figurative documents, fundamental from the historical point of view, regarding a long period between the beginning of the sixteenth century and the late twentieth century. In the second case, the atlas collects results of the work carried out by the GECO Lab of the University of Florence between 2013 and 2015, which illustrates the cave's complex hydraulic system and internal decorations. Regarding the photographic documentation carried out by GECO Lab, the images are the result of the processing of many photographs for obtaining overall high-resolution images. The panoramic image showing the whole Grotto in equirectangular projection is composed of 126 photographs, whereas the images of the basins are represented in a rectilinear projection in order to preserve the straight lines as in a normal photograph using central projection.